USING ONLINE TOOLS FOR EVALUATION THE DIGITAL COMPETENCE OF TEACHERS AND PRINCIPALS IN NORWAY - Iryna V. Ivanyuk (Information technologies and learning tools, 2015)
The article is devoted to the problems of digital competence evaluation in general secondary education in Norway. Attention is drawn to the fact that the monitoring and evaluation of digital competence of the participants of the educational process in secondary schools at the national level, specially created Norwegian Centre for ICT in education. The content and process using online tools for self-evaluation of digital competence of teachers and principals are described. The examples of estimation of digital competence through online tools «School Mentor» and «Teacher Mentor» on levels and proposed activities to improve are presented. The main approaches used in the formation of scale evaluation of the level of digital competence of the teacher are found out.